GovTech Maturity Index : The State of Public Sector Digital Transformation - Dener, Cem (Washington, DC: World Bank, 2021)
Governments have been using technology to modernize the public sector for decades. The World Bank Group (WBG) has been a partner in this process, providing both financing and technical assistance to facilitate countries’ digital transformation journeys since the 1980s. The WBG launched the GovTech Initiative in 2019 to support the latest generation of these reforms. Over the past five years, developing countries have increasingly requested WBG support to design even more advanced digital transformation programs. These programs will help to increase government efficiency and improve the access to and the quality of service delivery, provide more government-to-citizen and government-to-business communications, enhance transparency and reduce corruption, improve governance and oversight, and modernize core government operations. The GovTech Initiative appropriately responds to this growing demand. The GovTech Maturity Index (GTMI) measures the key aspects of four GovTech focus areas—supporting core government systems, enhancing service delivery, mainstreaming citizen engagement, and fostering GovTech enablers—and assists advisers and practitioners in the design of new digital transformation projects. Constructed for 198 economies using consistent data sources, the GTMI is the most comprehensive measure of digital transformation in the public sector. Several similar indices and indicators are available in the public domain to measure aspects of digital government—including the United Nations e-Government Development Index, the WBG’s Digital Adoption Index, and the Organisation for Economic Co-operation and Development (OECD) Digital Government Index. These indices, however, do not fully capture the aspects of emphasis in the GovTech approach—the whole-of-government approach and citizen centricity—as key when assessing the use of digital solutions for public sector modernization. The GTMI is not intended to be an assessment of readiness or performance; rather, it is intended to complement the existing tools and diagnostics by providing a baseline and a benchmark for GovTech maturity and by offering insights to those areas that have room for improvement. The GTMI is designed to be used by practitioners, policy makers, and task teams involved in the design of digital transformation strategies and individual projects, as well as by those who seek to understand their own practices and learn from those of others.